(untitled) (Jurnal Pembangunan Sosial, 2011)
The purpose of this study is to examine the connection between self-esteem and family relations with the level of depression, anxiety and stress amongst teenagers in public housing. Respondents for the study consist of 379 teenagers living in public housings in various parts of Federal Territory, Kuala Lumpur. Self-esteem was measured using Rosenberg Self-Esteem Scale (1965) while the Index of Family Relations by Hudson (1993) was employed to evaluate the relationships between family members. Depression, Anxiety and Stress Scale by Lovibond and Lovibond (1995) was used to measure the level of depression, anxiety and stress amongst the respondents. Data were analysed using descriptive analysis and Pearson Correlation. The findings of the study showed that teenagers have a medium level of self esteem, whilst majority of the respondents have problems with their family. The result showed that there was a significant relationship between selfesteem and depression, anxiety and stress. Family relations also played an important part in contributing to the level of depression, anxiety and stress amongst teenagers.